9. CHILDREN'S DISEASE PATTERNS AT CHILDREN'S HOSPITAL 2 IN 5 YEARS FROM 2018 TO 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: Determine the disease pattern of inpatients treated at Children's Hospital 2 from January 1, 2018 to December 31, 2022 in 3 stages: before the COVID-19 pandemic, during the COVID-19 pandemic, after the COVID-19 pandemic and for 5 years.Methods: Design a cross-sectional retrospective study to collect available primary data from medical records stored on hospital management software of pediatric patients receiving inpatient treatment at Children's Hospital 2 from January 1, 2018 to December 31, 2022.Results: Infectious diseases during the pre- and post-COVID-19 phases account for 49.5% and 48.5%, respectively. Non-communicable diseases during the COVID-19 phase and over the past 5 years account for 53.4% and 48.3%. Respiratory diseases (Chapter X) account for between 25.4% and 34.7% across the three phases of the pandemic and in the last 5 years. Pneumonia (J18) accounts for between 10.7% and 14.2% across the three phases of the pandemic and in the last 5 years.Conclusion: In the pre-COVID-19 and post-COVID-19 periods, infectious diseases were more prevalent than non-infectious diseases and injuries, poisoning and accidents. In the COVID-19 period and for 5 years, non-infectious diseases were more prevalent than infectious diseases and injuries, poisoning and accidents. Respiratory diseases (chapter X) were the most common disease chapter and pneumonia (J18) was the most common disease in all three periods.
Keywords: disease pattern, pediatric, ICD-10.